Hukuman Mati Terhadap Pelaku Terorisme (Analisis Sosiologi) - Asnawi Abdullah (STIS Ummul Ayman, Meureudu, Pidie Jaya, Aceh, Indonesia, 2021)
This study focuses on an Islamic review of the relevant punishments for perpetrators of terrorism, as well as what efforts need to be applied by the government or the authorities against them which have developed throughout the world and can disturb the public in almost all countries. This type of research is normative juridical with a qualitative approach while the data used are secondary data. The results of the study indicate that the controversy over the application of the death penalty to criminals has begun to be eliminated given the legal consequences for the application of the crime. Although later talking about the issue from a human rights perspective, there are violations, but from a deterrent effect, deeper considerations need to be made considering Indonesia's condition which is vulnerable to the development of terrorism.